Penentuan Kondisi Optimasi Transpor Ion Cu (Ii) Melalui Teknik Membran Cair Fasa Ruah Secara Simultan Dengan Oksin Sebagai Pembawa - -, Refinel; Alif, Admin; Octarini, Rizki (Universitas Andalas, 2011)
ABSTRACT Determination of optimum condition and kinetic analysis Cu (II) iontransport by simultaneous bulk liquid membrane has been studied. Optimum condition for resource phase with Cu (II) ion concentration as 3,147 x 10-4 M obtained at pH 3 receiving phase with H2SO4 concentration 0,15 M and transport time as long as 3 hours through chloroform membrane using oxine 17,5 x 10-4 M as carrier. Transportation rate of Cu (II) ion decided by comparasion changer-over rest concentration in resource phase Rs and transpoted to receiving phase Rp and then monitored by Atomic Adsorbtion Spectrophotometre (AAS). Kinetic of transport Cu (II) ion process by simultaneous bulk liquid membrane technique fulfil irreversible consecutive first order reaction with transport Cu (II) ion gave (k1) value as 0,0442 minute-1 and ( k1 ) 0,0372 minute-1 . Simultaneous bulk liquid membrane method can be the alternative method in the determination of optimum condition and kinetic analysis of metal ions transport. Key words: Cu (II) ion, kinetic, optimum, transport, liquid membrane, simultaneous